EKSPERIMENTASI MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) DAN THINK PAIR SHARE (TPS) DENGAN PENDEKATAN SAINTIFIK PADA MATERI FUNGSI DITINJAU DARI INTERAKSI SOSIAL - Cahyono, Heri; Mardiyana, Mardiyana; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
Abstract. The aim of the research was to determine the effect of learning models on mathematics achievement viewed from studentâs social interaction. The learning models compared were TAI with scientific approach, TPS with scientific approach, and classical with scientific approach. The type of the research was a quasi experimental research with the factorial design of 3 x 3. The population were all eight grade students of Junior High School in Ngawi regency on academic year 2014/2015. The sample consisted of students of SMPN 3 Ngrambe, SMPN 2 Paron, and SMPN 2 Widodaren, which taken by using stratified cluster random sampling technique. The data of the research were collected through documentation, questionnaire, and test. The data was analyzed using unbalanced two-ways anova at the significance level of 0,05. Based on the data analysis, it can be concluded as follows. (1) TAI with scientific approach gives better mathematics achievement than TPS with scientific approach and classical with scientific approach, TPS with scientific approach and classical with scientific approach gives same mathematics achievement. (2) Students with high social interaction have better mathematics achievements than students with medium social interaction and low social interaction, while students with medium social interaction have better mathematics achievements than students with low social interaction. (3) For TAI with scientific approach, students with high and medium social interaction have the same mathematics achievements, and both have better mathematics achievement than low social interaction. For TPS with scientific approach, students with high social interaction have better mathematics achievement than students with medium and low social interaction, and students with medium and low social interaction have the same mathematics achievement. For classical with scientific approach, students with high social interaction have better mathematics achievement than students with medium social interaction, and both have the same mathematics achievement as students with low social interaction. (4) For students with high and low social interaction, all learning models gives the same mathematics achievement. For students with medium social interaction, TAI with scientific approach gives better mathematics achievement than TPS with scientific approach and classical with scientific approach, TPS with scientific approach and classical with scientific approach gives the same mathematics achievement.Keywords: TAI with scientific approach, TPS with scientific approach, classical learning, social interaction, learning achievement.